The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1203/00006450-199210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Glutathione during Oxidative Stress in Erythrocytes of the Newborn

Abstract: ABSTRAO. The ability of erythrocytes from newborn babies and adults to maintain reduced glutathione levels during oxidative stress was studied. In vitro incubation of erythrocytes with H202, with or without inactivation of catalase, caused a rapid depletion of reduced glutathione (CSH) and concomitant accumulation of oxidized glutathione followed by recovery of CSH and fall of oxidized glutathione to initial values in all subjects. In vitro and in vivo studies have shown that the erythrocytes of adult animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…Though obtained with a different experimental protocol (t-BOOH instead of H 2 O 2 ), the results of GSH recycling in newborns and adults were in good agreement with those obtained by other authors [14]. Using H 2 O 2 and RBC with inhibited CAT activity, Clahsen et al [14] found a shorter GSH recovery time in preterm than in term babies. Moreover, the GSH recovery time of preterm babies was correlated with the gestational age at birth.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Though obtained with a different experimental protocol (t-BOOH instead of H 2 O 2 ), the results of GSH recycling in newborns and adults were in good agreement with those obtained by other authors [14]. Using H 2 O 2 and RBC with inhibited CAT activity, Clahsen et al [14] found a shorter GSH recovery time in preterm than in term babies. Moreover, the GSH recovery time of preterm babies was correlated with the gestational age at birth.…”
Section: Discussionsupporting
confidence: 79%
“…CAT, GPX, and SOD activities did not differ between adults and newborns (table 3). A greater GR activity in neonates than in adults has also been found by other authors [14]. CAT and GPX activities were lower in erythrocytes of newborn babies than in RBC of adults, but not statistically significantly.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, the increased total GSH concentration in the late group cannot be explained by different recycling rates between the groups. Moreover, recycling of oxidized GSSG back to GSH seems to be enhanced rather than decreased in preterm infants (23,24). Consequently, the increased GSH concentration is likely to be caused by decreased consumption of GSH after early AA administration in preterm infants.…”
Section: Discussionmentioning
confidence: 99%